Deciphering genomic complexity: Understanding intratumor heterogeneity, clonal evolution, and therapeutic vulnerabilities in oral squamous cell carcinoma - Vishnu Priya Veeraraghavan; Bharati R. Doni; Arun Kumar Dasari; Chaitra Patil; Krishna A. Rao; Santosh R. Patil (Oral Oncology Reports)
Oral squamous cell carcinoma (OSCC), which is characterized by high rates of recurrence and metastasis, is a prevalent and burdensome form of head and neck cancer. Genomic heterogeneity and clonal evolution play critical roles in OSCC progression and therapeutic resistance. This review comprehensively examines the current understanding of genomic heterogeneity in OSCC, focusing on intratumoral heterogeneity and clonal evolution. Key driver mutations and therapeutic vulnerabilities were identified using next-generation sequencing and functional genomics approaches. The clinical implications include personalized treatment approaches, prognostic biomarkers, and targeted therapy selection. Challenges, such as intratumor heterogeneity and acquired resistance, are discussed, along with future directions for therapeutic strategies. The integration of genomic profiling into clinical practice enhances risk assessment, treatment outcomes, and patient care in OSCC management.